Assessing the prospect of a common PPP framework for ASEAN - Abdul Rashid, Khairuddin (2015)
ASEAN aspires to achieve regional economic integration by 2020 (ASEAN Economic Community or AEC). The most significant target of the AEC is perhaps the establishment of a well-connected, highly competitive and resilient ASEAN wherein people, goods, services and capital are closer together. Infrastructure therefore is urgently needed. Among the constraints in establishing infrastructure is the inability of member countries to provide adequate funding. Consequently, they entice their private sectors to assist through the provision of funds as well as expertise. Public-Private cooperation via the Public Private Partnerships or PPP is seen by ASEAN as among the most viable alternative. This paper, prepared via desk research, examines PPP implementation in ASEAN member countries and assesses the prospect of having a common PPP framework for ASEAN. In conducting the assessment PPP implementation framework within the European Union (EU) is used as benchmark. The key findings include that country specific PPP implementation framework exits in each ASEAN member countries but the framework differs from one country to another. In addition, ASEAN member countries are at different stages of PPP implementation maturity. The diverse PPP implementation framework may not be beneficial or could even act as among the impediments towards the realization of AEC 2020. The paper concludes with views on the prospect of a common PPP implementation framework for ASEAN and highlights, for initial consideration, key areas considered apt to be harmonized.